Green Concept of Kulon Progo Airport Development using UMI Simulation - Sri Mulyani; Rianto Rianto; Bangga Dirgantara Adiputra (Institut Teknologi Dirgantara Adisutjipto, 2023)
High energy consumption on the airport becomes a very crucial issue nowadays. Uninterruptable energy supply is required to support airline’s activity and keep the passenger convenience. Regarding the mentioned problem, there is a need to enhance the current plan of the airport with green airport concept. Green airport concept also known as eco-airport is an airport that adopted green and sustainable ecosystem concept to integrate community and environment that lead to reduction of energy consumption. The blueprint of Kulon Progo airport with green concept located in D.I. Yogyakarta, Indonesia has been made and the construction started in the mid of 2016. The airport has a FAR of 0.16 with 637 hectares land area. This study is simulating the plan to assess the energy consumption and CO2 emission in each part of the building in Kulon Progo Airport using Urban Modeling Interface simulator. From the results, it can be seen that the passenger terminal building is responsible for the highest share with 1,351,861.01 Kwh while second floor of ATC building has the highest CO2 emission 2,679.77 kgCO2/m